2005
DOI: 10.1080/14992020500147615
|View full text |Cite
|
Sign up to set email alerts
|

Psychometrically equivalent mandarin bisyllabic speech discrimination materials spoken by male and female talkers

Abstract: The purpose of this study was to develop, digitally record, evaluate, and psychometrically equate a set of Mandarin bisyllabic word lists for use in measurement of speech discrimination. Familiar bisyllabic words were digitally recorded by male and female talkers of Standard Mandarin. Percentage of correct word recognition was measured for each word at ten intensity levels ( -5 to 40 dB HL) in 5 dB increments using 20 normally hearing subjects. Using logistic regression, 200 words with the steepest logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…Martin, Champlin & Perez (2000) reported that speech discrimination scores for subjects with hearing impairment or normal hearing did not seem to be affected by whether the word list had phonetic balance or not. Hence, in terms of its relevance to speech recognition testing, the issue of phonetic balance is still an area of dispute (Nissen, Harris, Jennings, Eggett & Buck, 2005). However, the authors in the current study felt that phonemic balance is important at least for consonants.…”
Section: B Performance-intensity (Pi) Function Testingmentioning
confidence: 61%
“…Martin, Champlin & Perez (2000) reported that speech discrimination scores for subjects with hearing impairment or normal hearing did not seem to be affected by whether the word list had phonetic balance or not. Hence, in terms of its relevance to speech recognition testing, the issue of phonetic balance is still an area of dispute (Nissen, Harris, Jennings, Eggett & Buck, 2005). However, the authors in the current study felt that phonemic balance is important at least for consonants.…”
Section: B Performance-intensity (Pi) Function Testingmentioning
confidence: 61%
“…The performance-SNR psychometric functions were obtained based on the mathematical procedures described by Nissen, Harris, Jennings, Eggett, and Buck (2005). Logistic regression, as shown in Equation 1, was used to obtain the regression slope (b) and regression intercept (a) based on the proportion correct score ( p) at each signal-tonoise presentation level (SNR), for each of the test items from DI-WORD and TONE, and separately for the NF and NS conditions, for all participants.…”
Section: Discussionmentioning
confidence: 99%
“…retroflex suffix). Please refer to the companion paper in this journal for a more detailed description of the linguistic features of Standard Mandarin (Nissen et al, 2005).…”
Section: Sumariomentioning
confidence: 99%